Chemical generation of bispecific antibodies - Doppalapudi, Venkata R.; Huang, Jie; Liu, Dingguo; Jin, Ping; Liu, Bin; Li, Lingna; Desharnais, Joel; Hagen, Crystal; Levin, Nancy J.; Shields, Michael J.; Parish, Michelle; Murphy, Robert E.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Bispecific antibodies (BsAbs) are regarded as promising therapeutic agents due to their ability to simultaneously bind two different antigens. Several bispecific modalities have been developed, but their utility is limited due to problems with stability and manufacturing complexity. Here we report a versatile technology, based on a scaffold antibody and pharmacophore peptide heterodimers, that enables rapid generation and chemical optimization of bispecific antibodies, which are termed bispecific CovX-Bodies. Two different peptides are joined together using a branched azetidinone linker and fused to the scaffold antibody under mild conditions in a site-specific manner. Whereas the pharmacophores are responsible for functional activities, the antibody scaffold imparts long half-life and Ig-like distribution. The pharmacophores can be chemically optimized or replaced with other pharmacophores to generate optimized or unique bispecific antibodies. As a prototype, we developed a bispecific antibody that binds both vascular endothelial growth factor (VEGF) and angiopoietin-2 (Ang2) simultaneously, inhibits their function, shows efficacy in tumor xenograft studies, and greatly augments the antitumor effects of standard chemotherapy. This unique antiangiogenic bispecific antibody is in phase-1 clinical trials.